3D Crinkled Alk‐Ti3C2 MXene Based Flexible Piezoresistive Sensors with Ultra‐High Sensitivity and Ultra‐Wide Pressure Range. Issue 6 (22nd April 2021) - Xiang, Yucui; Fang, Liang; Wu, Fang; Zhang, Shufang; Ruan, Haibo; Luo, Haijun; Zhang, Hong; Li, Wanjun; Long, Xingming; Hu, Baoshan; Zhou, Miao
Abstract: The conflict between high sensitivity and wide sensing range greatly limits the extensive application of flexible pressure sensors. To produce a sensor with both high sensitivity and wide range is still a challenging work. Herein, flexible and highly sensitive piezoresistive sensors with wide sensing range are developed by combining the alkali‐treated 3D crinkled MXene with microstructured polydimethylsiloxane (PDMS). Sensors with different‐roughness PDMS films as flexible substrate and the unprocessed MXene as the conductive material are prepared to clarify the geometric design for the ultra‐wide pressure range (0–800 kPa). Then, other sensors assembled by NaOH‐alkalized 3D crinkled MXenes and rough PDMS are fabricated to illustrate that the material optimization can further enhance the sensitivity (up to 1104.38 kPa −1 ). The sensor shows a low limit of detection (17 Pa), fast response time (100 ms), good cycle stability (3000 cycles, 300 kPa), and can detect over a wide pressure range from that of the tiny pills, pulse, heartbeat, throat vibration, and the change of water weight, exhibiting a broad prospect in health monitoring systems and human‐machine interaction. Abstract : A high performance flexible piezoresistive sensor based on the novel 3D crinkled MXene named as Alk‐Ti3 C2 and polydimethylsiloxane (PDMS) is successfully developed. Due to higher pressure tolerance provided by PDMS substrates and more contact points offered by Alk‐Ti3 C2 with special structure, the sensor possesses both high sensitivity and wide working range, exhibiting an extensive application.